REPRESENTASI PATRIARKI DAN EKSPLOITASI PADA PEREMPUAN DALAM FILM ENOLA HOLMES 2 - Dwi Amanda, Visca; Rahardjo, Turnomo; Bayu Widagdo, Muhammad (Interaksi Online, 2024)
Equality of rights and opportunities for women has been pursued through various forms of business. The use of gender themes, such as in the film Enola Holmes 2, depicts the role of women in the economic sector who are exploited by various patriarchal cultural stereotypes. This research aims to analyze several scenes from the film Enola Holmes with representations of the struggle for equality and women's labor rights. The type of research used is descriptive qualitative with John Fiske's semiotic analysis method. The research findings show that several scenes display code at the reality level, namely gestures and expressions as well as the environment, at the representation level technical aspects such as camera, dialogue, lighting and editing are found, and at the ideological level, pariarchy and exploitation ideology is found through coding at the previous level. Research found that in the film Enola Holmes 2 female workers were represented as having no power due to the existence of a patriarchal cultural system in British society in the 1880s and this led to acts of exploitation by powerful parties such as match factory owners towards workers who worked in the factory.